Blockchain-based IoT architecture to secure healthcare system using identity-based encryption - Sharma, Pratima; Moparthi, Nageswara Rao; Namasudra, Suyel; Shanmuganathan, Vimal; Hsu, Ching-Hsien (John Wiley and Sons Inc, 2022)
Nowadays, blockchain and Internet of Things (IoT) are two emerging areas of the Information Technology (IT) sector. These two emerging areas are used in various fields, such as supply chain, logistics and automotive industry. Due to the low processing power and storage space of IoT devices, users' medical information is usually saved in a centralized third party like a clinical repository or a cloud computing environment. Thus, in many cases, users lose control of their medical information, which can result in security disclosure and a single-point impediment. So, an advanced solution is required to improve the data sharing process, while restricting it in terms of security. Blockchain technology with IoT can significantly affect the healthcare industry by improving its efficiency, security and transparency, as well as can provide more business opportunities. The efficient sharing of Electronic Health Record (EHR) can improve the treatment process, diagnosis accuracy, security and privacy. This article proposes a blockchain-based IoT architecture to provide enhanced security of healthcare data by using Identity-Based Encryption (IBE) algorithm. Here, the smart contract defines all the basic operations of the healthcare system, which can be beneficial to all stakeholders. Many experiments are executed to evaluate the efficiency of the proposed scheme. The results show that the proposed scheme is better than the existing renowned schemes.
Keywords: electronic health record; ethereum; smart contract; swarm; Scopus; JCR